THE PERCEPTION OF RELIGIOUS LEADERS IN MAINTAINING THE HARMONIZATION IN ACEH: AN ANALYSIS OF SIYASAH SYAR’IYYAH - Fauzi Fauzi (Universitas Muhammadiyah Metro, 2018)
Aceh currently experiences dynamic situations within inter-and intra-religious adherents. Aceh, however, has proved itself throughout the history as the reliable place for any religious adherents. In order to restore the Aceh condition to its normal state, the cooperation between the government and the religious leaders will be among the important influencing factors. In this study, the role of the leaders in regard to the harmonization of the religious followers in Aceh. Findings showed that, first, the condition of Aceh was still perceived as harmonious, although with a little dynamic. Second, the conflicts occurred among religions in Aceh were generally caused by the external factors, although a small portion of the economic and socio-cultural aspects also had some influence. And, third, the religious leaders have not worked optimally yet to sustain the harmonization in Aceh. It’s need the leaders because, first, they have more knowledge on the condition and aspiration of their followers; second, they can share information on the followers’ real condition for the governor’s consideration in the new regulations, programs, and so forth; and third, they possess a sacred authority that can be used to calm any conflict.